2016
DOI: 10.17577/ijertv5is010350
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Application of Pulse Current Gas Metal Arc Welding Process for Preparation of Weld Joint with Superior Quality

Abstract: Quality of weld joint in the form of its mechanical and metallurgical properties produced using gas metal arc welding process is governed by combination of parameters employed. These parameters also affect arc stability, bead appearance and thermal and metal transfer behaviour. For a given shielding gas, diameter and composition of filler wire, different modes of metal transfer that can be achieved are short circuit, globular, spray and pulsed spray. The spray metal transfer provides better ease of operation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The evidence of LAHW application to weld large scale great thickness plates can be clearly seen in some cases like the study of Agrawal [48], where a joint with 25 m length was performed. Thus, it is indicated that for the execution of such joint with autogenous laser process (without the use of filler material) it would be required to maintain a maximum separation of 0.3 mm along the entire joining zone (25 m), being in this case almost unfeasible from a practical point of view.…”
Section: Gradementioning
confidence: 98%
See 4 more Smart Citations
“…The evidence of LAHW application to weld large scale great thickness plates can be clearly seen in some cases like the study of Agrawal [48], where a joint with 25 m length was performed. Thus, it is indicated that for the execution of such joint with autogenous laser process (without the use of filler material) it would be required to maintain a maximum separation of 0.3 mm along the entire joining zone (25 m), being in this case almost unfeasible from a practical point of view.…”
Section: Gradementioning
confidence: 98%
“…The concise achievable penetration depends on the characteristics of the laser source used; LAHW usually allows welding relatively high plate thicknesses (in the order of 10 to 15 mm) [21]. Hybrid welding is proposed as ideal joining process for large-scale applications, such as those required in the building of chemical tankers, gas or oil tankers, since thickness of material to be welded is usually greater than 20 mm [48].…”
Section: Lahw In Shipbuildingmentioning
confidence: 99%
See 3 more Smart Citations